Energy expenditure and food consumption of foraging Imperial cormorants in Patagonia, Argentina - Gómez Laich, Agustina Marta; Wilson, Rory P.; Shepard, Emily L. C.; Quintana, Flavio Roberto (Marine Biology)
Energy management during the breeding season is crucial for central place foragers since parents need to feed themselves and their offspring while being spatially and temporally constrained. In this work, we used overall dynamic body acceleration as a measure of activity and also to allude to the foraging energy expenditure of breeding Imperial cormorants Phalacrocorax atriceps. We also analyzed how changes in the time or energy allocated to different activities affected the foraging trip energy expenditure and estimated the daily food requirements of the species. Birds spent 42 % of the total energy flying to and from the feeding areas and 16 % floating at sea. The level of activity underwater was almost 1.5 times higher for females than for males. The most expensive diving phase in terms of rate of energy expenditure was descending though the water column. The total foraging trip energy expenditure was particularly sensitive to variation in the amount of time spent flying. During the breeding season, adult cormorants breeding along the Patagonian coast would consume approximately 10,000 tons of food. Fil: Gómez Laich, Agustina Marta. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Wilson, Rory P. University of Wales. Institute of Environmental Sustainability. Biological Sciences; Reino Unido Fil: Shepard, Emily L. C. University of Wales. Institute of Environmental Sustainability. Biological Sciences; Reino Unido Fil: Quintana, Flavio Roberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina